The apostle [videorecording (DVD)] - Duvall, Robert; Fawcett, Farrah, 1947-2009; Allen, Todd, 1960-; Cash, June Carter, 1929-2003; Thornton, Billy Bob; Richardson, Miranda (Universal Studios, 2003)
Sonny is a gifted Southern Pentecostal preacher loved by his community in Texas. When Sonny loses control and commits a crime of passion, he is forced to run from the law. Hiding out in the small Louisiana town of Bayou Boutte, Sonny adopts a new identity as the Apostle E.F. and sets out on a new mission-- to find the road to redemption.